Low‐Dose Lipopolysaccharide Causes Biliary Injury by Blood Biliary Barrier Impairment in a Rat Hepatic Ischemia/Reperfusion Model. Issue 2 (11th January 2017) - Reiling, Janske; Bridle, Kim R.; Gijbels, Marion; Schaap, Frank G.; Jaskowski, Lesley; Santrampurwala, Nishreen; Britton, Laurence J.; Campbell, Catherine M.; Olde Damink, Steven W. M.; Crawford, Darrell H. G.; Dejong, Cornelius H. C.; Fawcett, Jonathan
Abstract : This study explored whether bacterial endotoxins, in the form of lipopolysaccharides (LPS), could have an injurious effect on the biliary tract in conjunction with ischemia. A total of 64 rats were randomly assigned to 4 groups: sham operation (sham group), 1 mg/kg LPS intraperitoneal (LPS group), hepatic ischemia/reperfusion (IR; IR group), and IR combined with LPS (IR+LPS group). Following 1 or 6 hours of reperfusion, serum liver tests, bile duct histology, immunofluorescence microscopy (zonula occludens‐1 [ZO‐1]), bile composition (bile salts, phospholipids, lactate dehydrogenase), hepatic gene expression (bile salt transporters and inflammatory mediators), as well as serum and biliary cytokine concentrations were quantified and compared between the study groups. In addition, the integrity of the blood biliary barrier (BBB) was assayed in vivo using horseradish peroxidase (HRP). LPS administration induced severe small bile duct injury following 6 hours of reperfusion. Furthermore, total bile salts and bilirubin concentrations in serum were increased in the LPS groups compared with sham controls (LPS, + 3.3‐fold and +1.9‐fold; IR+LPS, + 3.8‐fold and +1.7‐fold, respectively). The BBB was impaired in the LPS groups as evidenced by elevated levels of HRP in bile (+4.9‐fold), and decreased expression of claudin 1 (–6.7‐fold) and claudin 3 (–3.6‐fold). LPS was found to be a potent inducer of small bile duct injury following hepatic ischemia and 6 hours of reperfusion. This injury was associated with increased permeability of the BBB and impaired hepatic bile salt clearance. Liver Transplantation 23 194–206 2017 AASLD